KONSEP HARMONI SEBAGAI INOVASI DESAIN BANGUNAN GEREJA GMIT IMANUEL OEMORO, KABUPATEN KUPANG - Richardus Daton; Budhi Benyamin Lily; Aryanto Karmakani (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2023)
Abstract: The design of the Church Building needs to be done correctly and can accommodate the needs and potential according to the local context. The problem experienced by the community at GMIT Imanuel Oemoro is that there is an image of a church design that is not in accordance with community values and the local context. The aim of this research is to present a church design concept that is in accordance with the values and context of the Oemoro people. The research method was carried out in a qualitative descriptive manner by prioritizing inductive data. The author plays a direct role as the Planning Team and records all the potential and problems of the community or congregationÂ toÂ beÂ accommodatedÂ inÂ theÂ designÂ conceptÂ ofÂ theÂ GMITÂ ImanuelÂ OemoroÂ church building. The results of the study show that Harmony is the right concept as an innovative step in designing today's church buildings that can combine the values of people's lives in relation to others, nature and God. Harmony with nature in the use of local materials, namely river stone on building facades and fringes on ceiling materials and acoustic settings. Harmony with others in the interior arrangement of the church which prioritizes the principle of equality in the arrangement of furniture. Harmony with God is by applying the meaning of the word Immanuel which means